On the Stereochemical Course of Palladium-Catalyzed Cross-Coupling of Allylic Silanolate Salts with Aromatic Bromides - Denmark, Scott E. (2010)
The stereochemical course of palladium-catalyzed cross-coupling reactions of an enantioenriched, α-substituted, allylic silanolate salt with aromatic bromides has been investigated. The allylic silanolate salt was prepared in high geometrical (Z/E, 94:6) and high enantiomeric (94:6 er) purity by a copper-catalyzed S(N)2’ reaction of a resolved allylic carbamate. Eight different aromatic bromides underwent cross-coupling with excellent constitutional site selectivity (γ) and with excellent stereospecificity. Stereochemical correlation established that the transmetalation event proceeds through a syn S(E)’ mechanism which is interpreted in terms of an intramolecular delivery of the arylpalladium electrophile through a key intermediate that contains a discrete Si–O–Pd linkage.